Facile synthesis of rubrolide E - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
A simple and efficient synthesis of rubrolide E (1e) has been demonstrated via Meerwein coupling reaction of para-anisyl-diazonium chloride with N-phenylmaleimide (2), regioselective reduction of para-anisylmaleic anhydride (4), Knoevenagel condensation of butyrolactone 5 with para-anisaldehyde and demethylation pathway.
Keywords: Knoevenagel condensation; Meerwein coupling; N-phenylmaleimide; regioselective reduction; rubrolide E; Total synthesis

Facile synthesis of 1,3,7-trihydroxyxanthone and its regioselective coupling reactions with prenal: simple and efficient access to osajaxanthone and nigrolineaxanthone F - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2006)
A facile five-step synthesis of naturally occurring 1,3,7-trihydroxyxanthone has been described starting from 1,3,5-trimethoxybenzene via NBS-induced nuclear bromination, lithiation followed by an in situ benzoylation with methyl 2,5-dibenzyloxybenzoate, selective deprotection of the two benzyl groups, base-catalyzed intramolecular cyclization, and demethylations pathway with 62% overall yield. The regioselective coupling reactions of 1,3,7-trihydroxyxanthone with prenal in the presence of calcium hydroxide at room temperature and under thermal conditions at 140-150 degrees C have been demonstrated to exclusively obtain the natural products osajaxanthone in 75% yield and nigrolineaxanthone F in 98% yield, respectively.

Facile two-step chemoenzymatic access to natural germination inhibitor (+)-erigeronic acid A - Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2006)
A facile two-step synthesis of natural germination inhibitor 5-butyl-3-oxo-2,3-dihydrofuran-2-yl-acetic acid [(+)-erigeronic acid A, 1] has been described via highly regioselective ring opening of (R)-acetoxysuccinic anhydride with the primary enolate of butyl methyl ketone, followed by an enzymatic hydrolysis and ail in situ dehydrative cyclization pathway with 77% overall yield. Oil the basis of the present chemoenzymatic approach, (R)-configuration has been assigned to the C-2 chiral centre of the natural erigeronic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: (+)-erigeronic acid; (R)acetoxysuccinic anhydride; natural germination inhibitor; primary enolate of butyl methyl ketone; synthesis

Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.

Facile phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2+2] annulation reactions: an easy access to complex bioactive natural and unnatural benzopyran congeners - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
The complex bioactive natural and unnatural benzopyran congeners have been synthesized using one-/two-step approaches in very good yields from the reactions of two different dihydroxyphthalides, natural resorcyclic acid derivative, and trihydroxybenzophenone with citral and/or farnesal, via the phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions and three different thermal intramolecular cyclization reactions. The effects of the nature and the position of phenolic groups in the starting materials on the course of these cycloaddition reactions have also been described. Depending upon the absence or presence of intramolecular hydrogen bonding of the phenolic group with the carbonyl moiety in the starting materials, these phenol-driven intramolecular thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions either furnished the kinetically controlled products or directly formed the thermodynamically controlled rearranged products, respectively.

Facile S(N)2 ' coupling reactions of wittig reagents with dimethyl bromomethylfumarate: synthesis of enes, dienes, and related natural products - Patel, Ramesh M.; N. P. Argade (Journal of Organic Chemistry, 2007)

Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

Facile biogenetic synthesis of pulcheotine A - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2008)
Starting from homopiperonylamine and 4-methoxyphenylacetic acid, a facile biogenetic route to naturally occurring pulcheotine A has been demonstrated via Pictet-Spengler cyclization and two different air oxidation processes.
Keywords: 4-methoxyphenylacetic acid; homopiperonylamine; Pictet-Spengler cyclization; pulcheotine A; regioselective air oxidations

Facile approach to diverse range of 1,3-diaza-heterocycles: angular/linear selectivity paradigm and a remarkable intramolecular methyl migration - Kshirsagar, Umesh A.; N. P. Argade (Tetrahedron, 2009)
Starting from cyclic anhydrides and tert-butyl 2-aminobenzylcarbamate, simple and efficient synthesis of diverse range of kinetically controlled angular and thermodynamically controlled linear tricyclic and tetracyclic 1,3-diaza-heterocycles have been described via the intramolecular cyclizations of the corresponding imides/anilic acid esters. The effect of imide stability on the angular/linear product selectivity has also been described. The kinetically controlled angular products were successfully transformed to the corresponding thermodynamically controlled linear products by refluxing in methanol or methanol and acetic acid mixture. An interesting in situ 1,2-intramolecular methyl group migration has also been described. (C) 2009 Elsevier Ltd. All rights reserved.

Facile synthesis of oxyavicine - Jangir, Ravi; N. P. Argade (RSC Advances, 2012)
Starting from dimethyl 3,4-methylenedioxyhomophthalate, a concise total synthesis of oxyavicine has been described via the base catalyzed monoalkylation, homophthalimide formation, oxidative selective iodination, regioselective reductive dehydration and an intramolecular Heck coupling reaction followed by the oxidation pathway with 16% overall yield in six steps.

Facile synthesis of the isoquinoline alkaloids doryanine and oxyhydrastinine - Jangir, Ravi; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
Starting from 4,5-(methylenedioxy)homophthalic acid, a concise and efficient synthesis of the isoquinoline alkaloids dory-anine and oxyhydrastinine is described via the corresponding homophthalimide utilizing a one-pot regioselective reductive dehydration and catalytic hydrogenation pathway.
Keywords: dehydration; homophthalic acid; homophthalimide; isoquinoline alkaloids; regioselective reduction

Formal synthesis of bioactive indole alkaloids eburnamonine, eburnaminol, and vindeburnol - Mondal, Pravat; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from (+/-)-3-acetoxyglutarimide, diastereoselective formal synthesis of indole alkaloids (+/-)-eburnamonine, (+/-)-eburnaminol, and (+/-)-vindeburnol have been demonstrated via a common intermediate (+/-)-1-hydroxy-12-tosyl-2,3,6,7,12,12b-hexahydroindolo[2,3a] quinolizin-4(1H)-one in very good overall yields. The acetoxy group from (+/-)-3-acetoxyglutarimide was first used to induce the diastereoselectivity and also as a latent source of ketone carbonyl group. The stereoselective eliminations, reductions, and intramolecular cyclizations were the involved key steps.
Keywords: cyclizations; eburnaminol; eburnamonine; elimination; hexahydroindoloquinolizinone; reduction; vindeburnol

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

Facile synthesis of indolizinoindolone, indolylepoxypyrrolooxazole, indolylpyrrolooxazolone and isoindolopyrazinoindolone heterocycles from indole and imide derivatives - Shelar, Santosh V.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2021)
Chemo-, regio- and diastereoselective coupling reactions of indole with imide derivatives leading to unique heterocyclic systems are demonstrated. Acid-induced 3-position coupling reactions of indole with cyclic imide derived lactamols followed by acid promoted 2-position cyclizations with the corresponding aldehydes are described to obtain the indolizinoindolones and benzoindolizinoindolones. Base induced 2-position coupling reactions of N-tosylindole with N-(2-iodoethyl)imides and the subsequent cyclizations provide indolylepoxypyrrolooxazole, indolylpyrrolooxazolone and indolyloxazoloisoindolone. Reductive cleavage of indolyloxazoloisoindolone to the corresponding alcohol followed by mesylation and base promoted N-cyclization affords the in situ air-oxidized pentacyclic product hydroxyisoindolopyrazinoindolone. A regioisomeric structural revision of the natural product from 1,2,5,6,7,11c-hexahydro-3H-indolizino[7,8-b]indol-3-one to 1,2,5,6,11,11b-hexahydro-3H-indolizino(8,7-b)indol-3-one is also reported in the present studies focussed on the methodologies for heterocyclic synthesis.